2021
DOI: 10.5603/fm.a2020.0069
|View full text |Cite
|
Sign up to set email alerts
|

Types of left brachiocephalic vein aberrations detected during cardiac implantable electronic device implantation procedures

Abstract: Background: Cardiac implantable electronic device (CIED) implantation procedures with transvenous lead placement afford an opportunity to observe vascular anatomic variations.The course of CIED implantation depends largely on morphometric and topographic characteristics of the relevant brachiocephalic vein (BCV), which is the left BCV in the case of lead insertion via the left clavipectoral triangle. This study aims to present left BCV anomalies arising from abnormal systemic vein embryogenesis and encountered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is well established that, by its complex embryological development, the brachiocephalic vein can show various arrangements, including an atypical superior location and duplication. [ 2 3 4 5 6 ] In our patient, the brachiocephalic veins joined anterior to the trachea, and no structures were trapped between them. We believe that it is unlikely for the brachiocephalic veins to cause airway compression, as they are soft vascular structures and likely to elongate as the child grows.…”
Section: Discussionmentioning
confidence: 63%
“…It is well established that, by its complex embryological development, the brachiocephalic vein can show various arrangements, including an atypical superior location and duplication. [ 2 3 4 5 6 ] In our patient, the brachiocephalic veins joined anterior to the trachea, and no structures were trapped between them. We believe that it is unlikely for the brachiocephalic veins to cause airway compression, as they are soft vascular structures and likely to elongate as the child grows.…”
Section: Discussionmentioning
confidence: 63%
“…Notably, no other cardiac structural abnormalities were observed in this case of anomalous LBCV. Prior retrospective studies on demographic characteristics of LBCV cases demonstrated a mean age of diagnosis of 4 years and 9 months with a male predominance of 1.5:1, but these studies are limited by sample size due to the rarity of this anomaly [1 , 4] . Risk factors for anomalous development of the LBCV are unknown, but are possibly similar to those associated with other congenital cardiac malformations, such as uncontrolled maternal diabetes, intrauterine alcohol or tobacco exposure, or chromosomal abnormalities [3] .…”
Section: Discussionmentioning
confidence: 99%